Utility of regional STR marker variations in Tunisian and sub-Saharan populations: insights into forensic and population genetics - Attaoui, Asma; Foddha, Hajer; Othman, Houcemeddine; Ben Abdennebi, Hassen; Haj Khelil, Amel (Frontiers in Bioinformatics, 2025)
IntroductionThis study investigates the genetic variability and forensic applicability of Short Tandem Repeat (STR) loci including autosomal, X and Y-STR markers, across distinct Tunisian regions and among sub-Saharan African populations. Our objectives were to examine the regional allelic diversity of STR markers in Tunisia, and to assess the utility of these markers for forensic differentiation between Tunisian and sub-Saharan African.MethodsTwenty two STRs were genotyped in 500 Tunisian individuals and 501 sub-Saharan corpses by capillary electrophoresis using commercial system kits. A Chi-square test for homogeneity was applied to assess allele distribution and Principal Component Analysis to assess geographical allele variations. Bioinformatic methods in R packages were used, such as Logistic Regression Model to predict geographic group membership and Random Forest models to evaluate the discriminative power of the analyzed STRs.Results and DiscussionStatistical analyses revealed significant allelic variability between Northern, Central, and Southern Tunisia for markers such as D1S1656, D8S1179, and CSF1PO. PCA illustrated a clear genetic distinction between Tunisian and sub-Saharan populations, largely attributable to geographical and historical gene flow barriers. LRM achieved high accuracy (95.96%) in predicting geographic affiliation. RF analysis identified DYS391 as highly discriminative in population differentiation. Our findings align with prior research on Tunisian genetic diversity and extend this knowledge by illustrating allelic frequency variations in order to establish region-specific databases.ConclusionThis study contributes valuable insights into the genetic structure of Tunisian and sub-Saharan populations, emphasizing tailored approaches in forensic practices.